Talent Management and Servant Leadership as Retention Strategies for Generation Z Employees in the Creative Industry: A Systematic Literature Review - Ristiani, Deliana; Muslim, Bintang Lazuardi Benteng Buana (Manajemen Bisnis, 2026)
This study aims to analyze the influence of leadership style and work motivation on the job satisfaction of Civil Servants (ASN) at the Department of Manpower, Transmigration, Energy, and Mineral Resources of Southwest Papua Province. The main problem addressed is the low level of job satisfaction among civil servants, which is suspected to be influenced by leadership style and work motivation. This research uses a quantitative approach with a survey method involving 35 ASN as respondents. The research instrument was a questionnaire tested for validity and reliability, and data were analyzed using multiple linear regression with SPSS. The results indicate that, simultaneously, leadership style and work motivation significantly affect ASN job satisfaction (R² = 0.948; F = 292.512; sig. 0.000). However, only work motivation has a significant partial effect, while leadership style does not. The conclusion is that work motivation is the most dominant factor in improving ASN job satisfaction. It is recommended that the institution prioritize strengthening work motivation to sustainably enhance performance.